Blueprint : Aqua Enterprise “Smart Aquarium” / Nurul Athirah Anuar - Anuar, Nurul Athirah (2020)
Smart Aquarium with latest technology and special techniques in one product which convenient for businessman in aquatic sector. Demand for this product is probably high because it can save time, energy, money and maintain a good condition for surrounding. In the current market, there are a few disadvantages from the existing product of aquarium. The aquarium usually does not attach with TDS meter that can automatically replace and refill the water when TDS level is high. Thus, we could not use it wisely and it is not multifunctional. Therefore, Smart Aquarium will make easier for the user to use it from the beginning until the final process. This product also provides the construction to use without worry about messy when use. Our product is totally necessary for nowadays